2000
DOI: 10.1055/s-2000-8262
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy - not useful to monitor cerebral oxygenation after severe brain injury

Abstract: Since its development more than twenty years ago, non-invasive near-infrared-spectroscopy (NIRS) has been widely used to monitor cerebral oxygenation. Despite of its growing number of users, the diagnostic value of near-infrared spectroscopy still remains unclear, especially in case of acute brain injury and long-term neuromonitoring, necessary during intensive care therapy. To evaluate quality and sensitivity of NIRS measurements compared to invasive ICP-, CPP- and regional brain tissue--pO2 (p(ti)O2) monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 15 publications
0
34
0
2
Order By: Relevance
“…As well, because of the cost effectiveness, portability, and ease of use of NIRS, it is an attractive noninvasive technique for evaluating cerebral function in a variety of experimental conditions and settings. Several investigators have used NIRS to evaluate cerebral oxygenation and blood volume changes in patients with neurological disorders, including traumatic brain injury (TBI) [17][18][19][20], stroke [21], brain tumors [22][23], and cerebral ischemia [23]. The clinical application of NIRS in patients with severe acute TBI has indicated that the technique must be used cautiously because of its limited sensitivity [18] and oscillations that are observed in the oxyHb signal [19].…”
Section: Introductionmentioning
confidence: 99%
“…As well, because of the cost effectiveness, portability, and ease of use of NIRS, it is an attractive noninvasive technique for evaluating cerebral function in a variety of experimental conditions and settings. Several investigators have used NIRS to evaluate cerebral oxygenation and blood volume changes in patients with neurological disorders, including traumatic brain injury (TBI) [17][18][19][20], stroke [21], brain tumors [22][23], and cerebral ischemia [23]. The clinical application of NIRS in patients with severe acute TBI has indicated that the technique must be used cautiously because of its limited sensitivity [18] and oscillations that are observed in the oxyHb signal [19].…”
Section: Introductionmentioning
confidence: 99%
“…8 -10 However, their accuracy remains controversial, and to date they have not achieved regular clinical use. 11,12 The theory behind NIRS has been described in detail previously. 13 When one measures from the adult head, changes in hemoglobin chromophore concentrations are derived from a composite block of illuminated tissue.…”
mentioning
confidence: 99%
“…Lower or no correlation was found after changing paCO 2 and administration of mannitol. The high failure rate and the limited sensitivity affect the clinical use of near-infrared spectroscopy as a suitable part of neuromonitoring after acute brain injury at the present time (8).…”
Section: Discussionmentioning
confidence: 99%